Rh(III)-catalyzed directed C–H bond amidation of ferrocenes with isocyanates - Takebayashi, Satoshi; Shizuno, Tsubasa; Otani, Takashi; Shibata, Takanori (Beilstein Journal of Organic Chemistry, 2012)
[RhCp*(OAc)2(H2O)] [Cp* = pentamethylcyclopentadienyl] catalyzed the C–H bond amidation of ferrocenes possessing directing groups with isocyanates in the presence of 2 equiv/Rh of HBF4·OEt2. A variety of disubstituted ferrocenes were prepared in high yields, or excellent diastereoselectivities.
Keywords: amidation; C–H activation; C–H functionalization; ferrocene; rhodium